The Connection Between SMEs Business Performance and their Accounting Procedures: A Literature Review Study - Channarika, Kan; Mardy, Serey (MultiTech Publisher, 2024)
This study of the literature looks at the connection between small and medium-sized businesses' (SMEs) business performance and their accounting procedures in the service sector. The study employs a systematic review methodology that includes a thorough screening procedure to find studies that match the inclusion criteria and a thorough search of academic databases using pertinent keywords. The data analysis entails a thematic examination of the chosen studies, with an emphasis on the kinds of accounting procedures that SMEs employ, the performance metrics that are employed to gauge the success of their businesses, and the degree to which accounting procedures and performance are correlated. The practical consequences imply that financial accounting methods can help SMEs in the service sector enhance their business performance. Nonetheless, it's important to give management accounting techniques a thorough evaluation. Investigating the moderating factors—such as the external environment and resource availability—that influence the relationship between accounting methods and business performance is one suggestion for further research.